Hubungan Resiliensi Akademik dengan Stres Akademik Mahasiswa Akhir di Universitas PGRI Adi Buana Surabaya - Riski, Shalsa Febby Eka; Mudhar, Mudhar (Universitas Nusantara PGRI Kediri, 2025)
Academic resilience and academic stress aim to maintain individual stability in dealing with all academic pressures by building resilience. The method used in this study is quantitative correlational. This study was located at Universitas PGRI Adi Buana Surabaya using the Academic Resilience Scale (ARS-30) scale developed by Cassidy (2016) and the Educational Stress Scale for Adolescent (ESSA) scale Sun (2011). Using a non-probability sampling technique. The focus of the study was taken on respondents according to the characteristics in the study. Respondents in the study were 139 out of 140 populations. The results of the analysis using the correlational hypothesis test r = -508 with a significance of 0.000 with these results can be stated that there is a fairly strong relationship, or in other words Ho is rejected and Ha is accepted. Meaning that the higher the level of academic resilience possessed by final semester students, the lower the students' academic stress.